Global Studies of Using Fecal Biomarkers in Predicting Relapse in Inflammatory Bowel Disease - Liu, Fang; Lee, Seul A.; Riordan, Stephen M.; Zhang, Li; Zhu, Lixin (Frontiers in Medicine, 2020)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract mainly comprising two forms including Crohn’s disease (CD) and ulcerative colitis (UC). IBD is a lifelong relapsing remitting disease and relapses occur at random patterns which are unpredictable. Faecal biomarkers have been increasingly used to assess disease activity in IBD due to their positive correlations with intestinal inflammation. Recent studies have also assessed the use of faecal biomarkers in predicting relapse and postoperative recurrence. This review provides information from global studies of using faecal calprotectin, lactoferrin and S100A12 to predict relapse in IBD. Strategies for further studies and the use of these faecal biomarkers for personalised management in IBD are also discussed.